2023
DOI: 10.3390/jcm12020628
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Breakthrough Infections in Health Care Workers: An Italian Retrospective Cohort Study on Characteristics, Clinical Course and Outcomes

Abstract: Background: The aim of this study was to determine the characteristics, clinical course and outcomes of COVID-19 breakthrough infections (BIs) among healthcare workers (HCWs) of an Italian University Hospital. Methods: A retrospective observational study was conducted on 6111 HCWs, from January 2021 to February 2022. The study population was offered the full vaccination with BNT162b2 mRNA COVID-19 vaccine. To allow return to work after BI, the protocol required one negative nasopharyngeal RT-PCR swab followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
8
9
0
Order By: Relevance
“…In our study, it was observed that the incidence and severity of COVID-19 was reduced among the fully vaccinated healthcare workers even during rising cases of Delta and Omicron variants in the district and this finding was similar to most of the contemporary and recent studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The Incidence of COVID-19 vaccine breakthrough infection among healthcare workers in our study was 7.9% in a year observation period which was similar to a study done by Paris et al with 4.4% over six months, Rahi et al at 8.7% and De Maria et al at 9.7% over one year and 20.2% over 2 years. 17,19,26,27 In studies done by Gurung et al and Bhavya et al, there was a significantly higher incidence of COVID-19 vaccine breakthrough infections among healthcare workers compared to our study which could be partly explained by increased awareness, better adherence to COVID-19 appropriate behaviour in our study and possibility of highly transmissible variants circulating among the participants of their study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study, it was observed that the incidence and severity of COVID-19 was reduced among the fully vaccinated healthcare workers even during rising cases of Delta and Omicron variants in the district and this finding was similar to most of the contemporary and recent studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The Incidence of COVID-19 vaccine breakthrough infection among healthcare workers in our study was 7.9% in a year observation period which was similar to a study done by Paris et al with 4.4% over six months, Rahi et al at 8.7% and De Maria et al at 9.7% over one year and 20.2% over 2 years. 17,19,26,27 In studies done by Gurung et al and Bhavya et al, there was a significantly higher incidence of COVID-19 vaccine breakthrough infections among healthcare workers compared to our study which could be partly explained by increased awareness, better adherence to COVID-19 appropriate behaviour in our study and possibility of highly transmissible variants circulating among the participants of their study.…”
Section: Discussionsupporting
confidence: 87%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The Incidence of COVID-19 vaccine breakthrough infection among healthcare workers in our study was 7.9% in a year observation period which was similar to a study done by Paris et al with 4.4% over six months, Rahi et al at 8.7% and De Maria et al at 9.7% over one year and 20.2% over 2 years. 17,19,26,27 In studies done by Gurung et al and Bhavya et al, there was a significantly higher incidence of COVID-19 vaccine breakthrough infections among healthcare workers compared to our study which could be partly explained by increased awareness, better adherence to COVID-19 appropriate behaviour in our study and possibility of highly transmissible variants circulating among the participants of their study. 16,18 On the contrary, several studies showed a lesser incidence of COVID-19 vaccine breakthrough infection among healthcare workers when compared with our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Healthcare workers are particularly at risk due to their frequent and close contact with infected patients, resulting in their high representation among COVID-19 cases prior to the availability of vaccines [ 7 ]. Breakthrough infections, referring to cases where vaccinated individuals become infected with SARS-CoV-2, were found to be significantly higher in nurses compared to other professional groups [ 8 ]. Due to waning immunity and the emergence of new variants, it is necessary to implement measures such as continuous screening and testing in healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…On December 12th, 2019, a new coronavirus (SARS-Cov2) emerged in China, sparking a pandemic of acute respiratory syndrome in humans, COVID-19 [ 15 , 16 , 17 ]. The COVID-19 pandemic represents a massive impact on human health, causing sudden lifestyle changes, through social distancing and isolation at home, with great social and economic consequences [ 18 , 19 , 20 ]. Optimizing public health during this pandemic requires not only knowledge from the medical and biological sciences, but also of all human sciences related to lifestyle and social and behavioral studies, including dietary habits and lifestyle [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%